Kajian Indeks Pembangunan Manusia sebagai Indikator Pengukuran Kualitas Sumber Daya Manusia di Provinsi Gorontalo - Muhammad Yusuf; Fitriyane Lihawa; Dewi Wahyuni K. Baderan (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
Human Resource Development (HRD) is one of the main priorities in realizing the progress of a region. The Human Development Index (HDI) is one of the indicators used to measure the quality of HRD. This study aims to analyze the quality of HRD in Gorontalo Province using the HDI as the main indicator. Secondary data from the Central Statistics Agency (BPS) were analyzed to measure three dimensions of the HDI, namely health, education, and decent living standards during the period 2019-2023. The results of the study showed an increasing trend in the HDI across all regions, although at varying rates. Gorontalo City recorded the highest HDI value, reflecting better development quality compared to other districts. Meanwhile, North Gorontalo had the lowest HDI, although there was an increase from year to year. Further analysis showed that significant disparities in the dimensions of health, education, and per capita expenditure between urban and rural areas were major challenges. This study suggests the need for equitable development through increasing access to health services, quality education, and economic infrastructure to reduce disparities between regions. These findings are expected to contribute to more inclusive policy-making for HRD development in Gorontalo Province.